2019
DOI: 10.1038/s41396-019-0500-2
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of microbial diversity in forest nitrogen cycling: diverse ammonifiers and specialized ammonia oxidizers

Abstract: We tested the ecosystem functions of microbial diversity with a focus on ammonification (involving diverse microbial taxa) and nitrification (involving only specialized microbial taxa) in forest nitrogen cycling. This study was conducted on a forest slope, in which the soil environment and plant growth gradually changed. We measured the gross and net rates of ammonification and nitrification, the abundance of predicted ammonifiers and nitrifiers, and their community compositions in the soils. The abundance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 79 publications
(81 reference statements)
1
36
1
Order By: Relevance
“…This result is in contrast to multiple previous studies which found that AOA are more abundant than AOB in soils and the main driver of nitrification in forest soils (Isobe et al, 2020;Lu et al, 2015) and agricultural soils (Leininger et al, 2006;Sterngren et al, 2015). In particular, an acidic pH below 5 was reported to favor AOA activity rather than AOB (Lu et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in contrast to multiple previous studies which found that AOA are more abundant than AOB in soils and the main driver of nitrification in forest soils (Isobe et al, 2020;Lu et al, 2015) and agricultural soils (Leininger et al, 2006;Sterngren et al, 2015). In particular, an acidic pH below 5 was reported to favor AOA activity rather than AOB (Lu et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…The relative abundance of an individual gene in each sample was calculated as copies of that gene per average bacterial genome after considering 16S rRNA gene copies per genome. Similar strategies of N-cycling pathway inference have been previously applied to microbial communities from tallgrass prairie (Mackelprang et al, 2018), forest (Isobe et al, 2020), and crop rhizospheres (Zhu et al, 2016), where the functional predictions were considered alongside other lines of evidence. Here, the relative abundance of a putative taxon harboring an individual pathway was calculated as reads of the taxon within the whole community after considering 16S rRNA gene copies per genome.…”
Section: Bacterial Community Analysis and Predictive Functional Profilingmentioning
confidence: 99%
“…It is well known that bacteria are important drivers for nitrogen fixation in soil [16]. Furthermore, they are also a part of several processes in the nitrogen cycle including nitrification, denitrification and ammonification [17,18]. Besides, forest soil bacteria are considered as crucial decomposers degrading organic material (cellulose, hemicellulose and pectin, for example) [19][20][21] and solubilizing soil macro-and micronutrients (such as phosphorus, potassium and sulfur) [15,22,23].…”
Section: Introductionmentioning
confidence: 99%